Cashmere Quality of Iranian Goat Breeds - H. R. Ansari-Renani (Faculty of Animal Science, Bogor Agricultural University, 2013)
This paper assesses the cashmere quality in different Iranian cashmere goat breeds to determine the scope for improvement of fiber quality. In April 2009 midside cashmere samples were taken from a total of 168 male and female cashmere goats of 1, 2, 3, and 4 yr of age. The goats were randomly chosen from Raeini, Birjandi, and Nadoushan breeds respectively from Kerman, South Khorasan, and Yazd provinces. Cashmere yield (CY) was determined from the percentage of weight of dehaired cashmere to weight of shorn fibre. Cashmere fiber diameter was analyzed using a projection microscope instrument. A general linear model including sex and age as fixed effects and breed as random effect was used to analyze the data and measure the relationships between different cashmere characteristics and fleece attributes. The overall means ± standard deviations were for cashmere yield (CY) 51.4%±1.5%, mean fiber diameter (MFD) 18.7±0.2 µm, coefficient of variation of fiber diameter (CVFD) 19.1%±0.3% and staple length (SL) 42.8±1.6 mm. One year old goats had finer cashmere than older goats. CVFD were higher in males and CY and SL were higher in young animals. Iranian cashmere goat breeds have an excellent SL but are relatively coarse. Given the differences between goats there seems to be substantial scope to improve the commercial value of cashmere.